2012
DOI: 10.1007/s00411-012-0448-3
|View full text |Cite
|
Sign up to set email alerts
|

Data for the Reference Man: skeleton content of chemical elements

Abstract: This study was undertaken to provide reference values of chemical element mass fractions in intact bone of Reference (European Caucasian) Man/Woman. The rib bone samples investigated were obtained from autopsies of 84 apparently healthy 15-58-year-old citizens (38 females and 46 males) of a non-industrial region in the Central European part of Russia who had suffered sudden death. The mass fractions (mg/kg given on a wet mass basis) of 69 elements in these bone samples were measured by using neutron activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…The absence of potassium is not surprising since K + substitution for Ca 2+ in apatite is much less energetically favourable than sodium, due the relatively large size of the potassium ion 25 . This is consistent with the observation that potassium levels in bone are an order of magnitude less than sodium 26 . Zinc levels in bone are a further order of magnitude less than potassium 26 , and the four-fold enhancement observed in tumour tissue 21, 24 , to about 7–12 ppm, is unlikely to raise levels in calcifications to a level detectable by SEM-EDS.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The absence of potassium is not surprising since K + substitution for Ca 2+ in apatite is much less energetically favourable than sodium, due the relatively large size of the potassium ion 25 . This is consistent with the observation that potassium levels in bone are an order of magnitude less than sodium 26 . Zinc levels in bone are a further order of magnitude less than potassium 26 , and the four-fold enhancement observed in tumour tissue 21, 24 , to about 7–12 ppm, is unlikely to raise levels in calcifications to a level detectable by SEM-EDS.…”
Section: Resultssupporting
confidence: 92%
“…This is consistent with the observation that potassium levels in bone are an order of magnitude less than sodium 26 . Zinc levels in bone are a further order of magnitude less than potassium 26 , and the four-fold enhancement observed in tumour tissue 21, 24 , to about 7–12 ppm, is unlikely to raise levels in calcifications to a level detectable by SEM-EDS. Increased iron levels in tumours are very likely due to increased vascularity, as with zinc, the levels in bone and tumour soft tissue are far too small to make this a likely candidate for detection in this study.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…1). Table 2 [24][25][26][27][28] Chondrosarcoma is classified as a bone tumor. Our previous findings showed that the means of the Ca and P mass fraction in the chondrosarcoma tissue are lower than in normal bone, but the mean of Ca/P ratio is similar.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that tissues of the human body differ greatly in their proportions of chemical elements and that there is the homeostasis of element contents [11]. As was shown in our previous studies the human bone tissue contains much more Ca, P, Mg, and many other chemical elements in comparison with soft tissues [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Thus, it can be expected that normal bone and bone tumors, being different tissues have specific and different elemental compositions.…”
Section: Introductionmentioning
confidence: 96%